2011
DOI: 10.1038/nature10137
|View full text |Cite
|
Sign up to set email alerts
|

Role of YAP/TAZ in mechanotransduction

Abstract: Cells perceive their microenvironment not only through soluble signals but also through physical and mechanical cues, such as extracellular matrix (ECM) stiffness or confined adhesiveness. By mechanotransduction systems, cells translate these stimuli into biochemical signals controlling multiple aspects of cell behaviour, including growth, differentiation and cancer malignant progression, but how rigidity mechanosensing is ultimately linked to activity of nuclear transcription factors remains poorly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

244
5,150
23
38

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,557 publications
(5,641 citation statements)
references
References 82 publications
244
5,150
23
38
Order By: Relevance
“…Recent investigations have shown that YAP/TAZ behaves as cellular rheostats, which largely influence mechanosensing and affect cell function and fate 2, 40. For hMSCs in elastic hydrogels, YAP/TAZ mainly remained in the cytoplasm throughout the 7 d culture (Figure 5a,f and more representative images in Figure S11, Supporting Information), reminiscent of previous findings in slowly relaxing9 or nondegradable gels 38.…”
supporting
confidence: 78%
“…Recent investigations have shown that YAP/TAZ behaves as cellular rheostats, which largely influence mechanosensing and affect cell function and fate 2, 40. For hMSCs in elastic hydrogels, YAP/TAZ mainly remained in the cytoplasm throughout the 7 d culture (Figure 5a,f and more representative images in Figure S11, Supporting Information), reminiscent of previous findings in slowly relaxing9 or nondegradable gels 38.…”
supporting
confidence: 78%
“…To first investigate this hypothesis, old and young fibroblasts were cultured on collagen‐coated plates for 3–4 days and then fixed for evaluation of YAP/TAZ expression. YAP/TAZ are transcriptional regulators that relay mechanical signals imposed by the matrix and act as mediators of mechanotransductive signaling (Dupont et al ., 2011; Aragona et al ., 2013). Indeed, we find that aged fibroblasts display an increased nuclear translocation of YAP/TAZ (Fig 4D).…”
Section: Resultsmentioning
confidence: 99%
“…These age‐related alterations affect stem cell behavior, and both the aged ECM and matricellular proteins secreted by aged fibroblasts drive MuSC differentiation toward a fibrogenic lineage. Aged fibroblasts display an increased nuclear translocation of Yes‐associated protein (YAP)/transcriptional coactivator with PDZ‐binding motif (TAZ), mechanotransductive transcriptional regulators that are activated in response to a stiff microenvironment (Dupont et al ., 2011). Accordingly, seeding young fibroblasts onto a substrate engineered to mimic the stiffness of aged muscle drives YAP/TAZ nuclear translocation and promotes a secretory profile that favors MuSC fibrogenesis at the expense of myogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have elucidated two independent signal transduction pathways that are regulated by the state of actin polymerization. The effectors of these pathways are transcription factors YAP and MRTF (Olson & Nordheim, 2010; Dupont et al ., 2011; Janmey et al ., 2013; Maller et al ., 2013). Both transcription factors are sequestered in the cytoplasm when bound to separate protein complexes that associate with monomeric G‐actin.…”
Section: Discussionmentioning
confidence: 99%
“…Both transcription factors are sequestered in the cytoplasm when bound to separate protein complexes that associate with monomeric G‐actin. Mechanical force generation through recruitment of G‐actin to actin filaments results in release of YAP or MRTF, which translocate to the nucleus to regulate expression of target gene (Olson & Nordheim, 2010; Dupont et al ., 2011; Maller et al ., 2013). …”
Section: Discussionmentioning
confidence: 99%